Emergent management of trauma - Bailitz, John; Scaletta, Tom (McGraw-Hill Medical, 2011)
Emergent Management of Trauma is an effective handbook on trauma evaluation and management covering the breadth of injuries. The book incorporates a crisp outline approach, abundant illustrations, and careful organization. It includes important management algorithms and covers major traumatic injuries literally from top to bottom. It focuses on trauma in children, pregnancy, and the elderly.